A study of profile of information sought through RTI act protocols in tertiary care hospital - Kore, Maruti R.; Masare, Monika S.; Shinde, R. R.; Bansode-Gokhe, Seema S. (International Journal Of Community Medicine And Public Health, 2018)
Background: This article attempts to study the profile of information seeks through RTI (right to information act) protocols in a tertiary care hospital of a metropolitan city. Methods: This hospital record –based cross sectional study was carried out in a tertiary care hospital in Metropolitan city during the period of one year. Results: Total 819 applications were received in the study period of 3 years out of which 30% (273) of applications were randomly selected for study using simple random sampling method. Analysis matrix was designed as per content mentioned in RTI applications and was modified. Data was collected by scrutiny of application received and was analyzed. There were total 273 applications filed by various profile of applicants out of which 56.8% resolved within 30 days, 2.2% within 35 days, 1.1% within 40 days, 2.9% within 45 days while 30% were pending/unresolved and 7% withdrawal by applicant itself. Most of the queries were personal (35.5%) followed by demanding type (24.9%), social type (19.8%), information queries (18.7%), private type (0.7%) and lastly of grievances type (0.4%). Conclusions: Encouraging accessibility to information is one of the major changes for the people, as it may; significantly shift the act from the “official secrets act” mindset to the “right to information act” mindset.